2004
DOI: 10.1677/erc.1.00665
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional modulation of the cell cycle and breast cancer

Abstract: In the USA, breast cancer accounts for approximately 30% of all cancers diagnosed in women and is the second leading cause of cancer death in women. An understanding of the molecular genetic events governing breast cancer lead to both prevention and intervention strategies in an attempt to reduce mortality and morbidity from breast cancer. The last three decades of medical research examining the molecular pathogenesis of cancers have provided compelling evidence for the universal disruption of the cell cycle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 194 publications
0
34
0
Order By: Relevance
“…Recently, non-genomic crosstalks between PPARg and cytoplasmic proteins, like extracellular signalregulated kinase (ERK) 1/2 and MAPK kinases, have been reported in cancer cells and functional importance has been given to the subcellular localization of PPARg (Burgermeister & Seger 2007, Papageorgiou et al 2007. However, the last three decades of medical research examining the molecular pathogenesis of cancers have provided compelling evidence for the universal disruption of the cell cycle in human tumors, and recent studies have demonstrated a critical interface between hormonal signaling and the cell cycle (Hilakivi-Clarke et al 2004). In this context, mitogens like insulin, via the IR, may promote the progression through the G1 phase by inducing competence of the cyclin D1/cyclin-dependant kinase 4 (CDK4) complex.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Recently, non-genomic crosstalks between PPARg and cytoplasmic proteins, like extracellular signalregulated kinase (ERK) 1/2 and MAPK kinases, have been reported in cancer cells and functional importance has been given to the subcellular localization of PPARg (Burgermeister & Seger 2007, Papageorgiou et al 2007. However, the last three decades of medical research examining the molecular pathogenesis of cancers have provided compelling evidence for the universal disruption of the cell cycle in human tumors, and recent studies have demonstrated a critical interface between hormonal signaling and the cell cycle (Hilakivi-Clarke et al 2004). In this context, mitogens like insulin, via the IR, may promote the progression through the G1 phase by inducing competence of the cyclin D1/cyclin-dependant kinase 4 (CDK4) complex.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…This dose was chosen based on our previous studies. In order to rule-out a proliferation component on cell migration, in some experiments 5 μg/ml of mitomycin C was added [15][16][17][18][19][20] min prior to the scraping to inhibit DNA synthesis and cell mitosis (Roche, Indianapolis, IN). In order to verify the effect of vitamin A on the migration following mechanical damage, the replacement of medium after scratching was made with standard medium or medium without glutamine (WG) with supplementation of vitamin A (0.01-100 nM) in absence of toxin A.…”
Section: Migration Assay In Intestinal Cellsmentioning
confidence: 99%
“…The eukaryotic cell cycle is divided into G1, S, G2 and M phases, and there are checkpoints occurring at different phases to allow progression to the next phase. The tumour suppressor proteins p53 and pRb, cyclins and cyclin-dependent kinases (Cdk) have detrimental effects on the progression of the cell cycle, as reviewed by Hilakivi-Clarke et al (2004).…”
Section: Cell-cycle Arrestmentioning
confidence: 99%